Atmospheric Aerosol Outbreak over Nicosia, Cyprus, in April 2019: New Look at Case Study - Yuliia Yukhymchuk; Gennadi Milinevsky; Ivan Syniavskyi; Ioana Popovici; Florin Unga; Jean Sciare; Franco Marenco; Michael Pikridas; Philippe Goloub (Geography, Earth Science and Environment: Research Highlights Vol. 6, 2025)
Cyprus Island located in the Eastern Mediterranean is one of these hotspots with semi-arid climate. Cyprus is affected by a mixture of various aerosol types such as dust particles from deserts, biomass burning aerosol from North-Eastern Europe, and anthropogenic pollution from urban Southeastern Europe and, certainly, marine aerosols could be observed over the island. Cyprus Island also is under high risk of forest fires. This paper aims to analyze the significant changes in atmospheric aerosol characteristics during the extreme aerosol outbreak event in April 2019 in the atmosphere of Cyprus. The aerosol optical depth (AOD), Ångström exponent (AE), single-scattering albedo, refractive index, size, and vertical distribution of aerosol particles during the event of intense aerosol advection were studied in detail. For this purpose, the ground-based observations of the sun-photometer AERONET Nicosia station, lidar measurements, and back trajectories of air movements calculated using the Hybrid Single-Particle Lagrangian Integrated Trajectory Model (HYSPLIT) were studied. For backward trajectory building, the HYSPLIT model with the meteorological data files from The National Oceanic and Atmospheric Administration (NOAA) Global Data Assimilation System (GDAS) was employed. To compare with background aerosol load conditions during the year, the available data of AOD and AE were used from the observations at the Nicosia AERONET site in the 2015–2022 period. On 23–25 April 2019, strong aerosol advection over Nicosia was detected according to lidar and sun- photometer observations. On 25 April 2019, the day with the largest aerosol contamination, the AOD value exceeded 0.9 at \(λ\) = 500 nm. Analysis of the optical and microphysical characteristics during the extreme event supported that the aerosol advection consists of mainly Saharan dust particles. This assumption was confirmed by the AOD versus AE variations, single-scattering albedo, refractive index, and size distribution retrievals, as well as lidar data and HYSPLIT backward trajectories, where air masses containing dust particles came mostly from North Africa. The analysis shows that the April 2019 event was one of the strongest aerosol surges that regularly take place in springtime in the atmosphere over Cyprus. A noticeable reduction in the effective radiative forcing caused by increasing aerosol amount during the aerosol dust outbreak was revealed. These results can be used to quantify the impact of aerosol dust as a forcing agent that induces rapid changes in regional radiative forcing in the atmosphere.